>matter joining subject< Choreographing with - Loimaala, Karoliina (My University, 2020)
This written section of my thesis work is based on the artistic part Purpling that premiered at the Theatre Academy 24.9.2019 in Theatre Hall. The written section departs from analysing the artistic part. It attempts to present leading questions that drove the artistic process, what kind of choreographic and bodily practices were engaged in throughout the process, leading chosen theoretical frameworks, personal remarks and experiences that have affected both artistic and writing processes. The written section attempts to focus on how choreographing with matter and human as both active, vibrant constitutions, materialises in an affective, rich, and constantly changing intra-action (defined by Karen Barad). It tries to ponder on what possibilities a thematic of moving subjectivities might offer in terms of ending the era of Anthropocene. In this written section I will: Centralise my artistic interests in choreographic realm to the concepts of thingness, polysemy of matter, breathing space and affected body. Observe these interests through theoretical frameworks offered specifically by Hélène Cixous, Erin Manning and Jane Bennett. Itemise my tendency to begin an artistic process and analyse how that reveals the constitutive ingredients of my choreographic thinking. Introduce the driving motives and questions for Purpling: A personal sensorial experience event of purpling defined by Erin Manning an interest towards working with soil a question about translation as an artistic method, regarding translating a reconstructed subjectivity of Hélène Cixous´ hysteric into a choreographic work. Analyse how a period spent in Brazil functioned as a premonition for the artistic process, through personal, sensorial experiences and the questions that arose. Observe how and where the choreographic work actualised while being framed by concepts of vibrant landscape, feeling with world, and being (with) mineral. Observe what kind of choreographic operations were needed when researching the thematic of a reconstructed subjectivity of Cixous´ hysteric and so being, moving subjectivity. Observe and analyse how to use a Lacanian division into imaginary, symbolic and Real as a choreographic grid and a compositional tool. Ponder on possible meanings behind the initial questions and a possible outcome of what this choreographic work is about, to me.
Keywords: relativity; feeling with world; intra-action; Discourse of hysteric; hybrid; translation; materia; subjektiviteetti; hysteerikko; kanssatunteminen; suhteisuus; intra-aktio; transformaatio; Matter.; Minerals; Subjectivity.; Hysteric; Choreography; Subjectivity; aine; subjekti (filosofia); koreografia; hybridit; käännökset; subjektiivisuus; mineraalit; Cixous, Hélène; Manning, Erin; Bennett, Jane; Lacan, Jacques; materia; mineraler; koreografi; hybrider; översättningar; subjektivitet; fi=koreografia|sv=koreografi|en=Choreography|